Phenomic, genomic and transcriptomic studies of quorum sensing Enterobacter asburiae L1 from fresh vegetables / Lau Yin Yin - Lau, Yin Yin (2017)
Bacterial communication or quorum sensing (QS) is achieved via sensing of QS signalling molecules consisting of N-acyl homoserine lactones (AHL) in most Gram-negative bacteria. In this study, Enterobacteriaceae isolates from fresh vegetables were screened for AHLs production. A total of twenty different bacterial colonies were isolated and identified by matrix-assisted laser desorption ionization-time of flight mass spectrometry. Preliminary screening demonstrated that one out of twenty isolates produces short chain AHLs. This AHL-producing bacterium which is known as Enterobacter asburiae L1 was isolated from Batavia lettuce leaves and was selected for further study. High-resolution triple quadrupole liquid-chromatography mass spectrometry (LC-MS/MS) analysis on E. asburiae L1 spent culture supernatant confirmed the production of N-butanoyl homoserine lactone (C4-HSL) and N–hexanoyl homoserine lactone (C6-HSL). To the best of my knowledge, this is the first report of AHL production by E. asburiae. To characterize the luxI/R homologues of E. asburiae L1, the complete genome of E. asburiae L1 (4.5Mbp in size) was sequenced using the single molecule real time sequencer and the whole genome sequence accuracy was verified by optical genome mapping technology. In silico analysis of the E. asburiae L1 genome revealed the presence of a pair of luxR and luxI homologues, designated as easR and easI. The 639 bp easI gene was cloned and overexpressed in Escherichia coli BL21 (DE3)pLysS. Heterologously expressed EasI protein (~25 kDa) activated AHL biosensor Chromobacterium violaceum CV026, indicating this EasI is a functional AHL synthase. LC-MS/MS analysis confirmed the production of C4-HSL and C6-HSL from spent culture supernatant of induced E. coli BL21 (DE3)pLysS harbouring the recombinant EasI, suggesting that EasI is indeed the AHL synthase of E. asburiae L1. A mutant E. asburiae L1 with deletion of the easI gene was constructed using Lambda Red recombination method. With the constructed L1-ΔeasI::Kan mutant strain, whole transcriptomic sequencing was performed using RNA-seq. Based on the RNA-seq data, a total of 128 genes and 112 genes were being significantly downregulated and upregulated, respectively in L1-ΔeasI::Kan strain. The easI null mutant was shown to be impaired in biofilm formation in comparison to its wildtype strain. In addition, phenotypic microarray (PM) was applied to obtain full metabolic profiles of E. asburiae L1 wildtype and mutant strains. The easI null mutant was found metabolically less active than wildtype strain when the peptide nitrogen source was utilized. Besides, L1-ΔeasI::Kan strain has gained more resistance towards several antimicrobial substances. The current study has laid the foundation for developing a deeper understanding in elucidating the roles of AHLs in E. asburiae L1 and to study the interaction of EasI with compounds demonstrating anti-QS properties. This could possibly provide a model for bacterial cell-cell communication among E. asburiae strains.